PENGENDALIAN PEREDARAN MINUMAN BERALKOHOL OLEH DINAS PERINDUSTRIAN DAN PERDAGANGAN KOTA PEKANBARU - Helda Khairiyah; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Circulation of alcoholic beverages in Pekanbaru when it still raises various problems, there are still some places like hotels, cafes, restaurants and entertainment venues that does not extend the permit the sale of alcoholic beverages, and the discovery of circulation and sale of alcoholic beverages that do not use consent as has been established. The purpose of this research is to know the control of the distribution of alcoholic beverages by the department of industry and trade and to know the factors that hamper the control of the distribution of alcoholic beverages by department of industry and trade. The concept is used the process control by Stoner and Wankel in (Siswanto, 2011) which consists of setting the desired results, determine predictors, establish norms for predictors and the results, determine the information and feedback, and assess information and improvement. The research method used is the kind of research a qualitative approach to descriptive, the source using a technique Purposive sampling. The collection of data through interviews, observations, and documentation. The results of the department of industry and trade as controller in the distribution of alcoholic beverages has not shown a level that is optimal. Factor in the opposite direction and that is the lack of coordination with relevant agencies, the lack of facilities and infrastructure, lack of control function and out of public participation. Instead of the more optimally the department of industry and trade, more assertive in controlling the circulation of alcoholic beverages and businesses and communities should also support the department of industry and trade in controlling the circulation of alcoholic beverages in Pekanbaru City.Keywords : Controlling, Circulation, Alcoholic Beverages